Virtually Real: Cinematographic Verisimilitude within the Construct of Artistic Referentiality - Maddock, Daniel (Quarterly review of film and video, 2021)
Maddock detailes the history of the desire for realistic images in the lens-based practices of photography, and then cinematography, starting with the invention of the still photograph and its definition as an icon in 1894 by semiotician Charles Sanders Peirce. Since Peirce related the photograph by physical connection to the reality it was capturing practitioners of lens-based arts have pursued realistic imagery. Though the term realism has been used frequently throughout the history of lens-based practices it is actually incorrect to describe images in this way as a recorded image cannot be real in the same way the event the camera used to make the image was real. The term real can more clearly be replaced with verisimilar. Further, using Neale's definition, the images of lens-based practices are culturally verisimilar, that is to say that culturally verisimilar images are plausible within the cultural or historical context of the real world, even if those images are of fictional narrative. The introduction of virtual means of altering images caused much controversy in recent years, especially wherein the definition of the practice of cinematography is concerned.